Half-width and line center shifts formed by transitions into highly excited vibration states of CO molecule; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Stroinova V. N. (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа